2015
DOI: 10.1515/bmt-2014-0139
|View full text |Cite
|
Sign up to set email alerts
|

How physical infusion system parameters cause clinically relevant dose deviations after setpoint changes

Abstract: Multi-infusion therapy, in which multiple pumps are connected to one access point, is frequently used in patient treatments. This practice is known to cause dosing errors following setpoint changes in the drug concentrations that actually enter the patients. Within the Metrology for Drug Delivery Project, we analyzed and quantified the two main physical phenomena leading to these errors: the "push-out" effect and the system mechanical compliance. We compared the dosing errors of a three-pump system with two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Although both these quantities exceed the maintenance dose, only the unclamped situation is likely to produce the hypertensive crisis as shown in Figure 2. Moreover, clinicians should note that in these cases, a second overdose may occur because the ratio in concentration between the saline and the norepinephrine pump is temporarily changed at the mixing point of the infusion set along with the flow rate deviation, 6 which only occurred in the norepinephrine pump in the described case.…”
Section: Advice and Clinical Considerationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although both these quantities exceed the maintenance dose, only the unclamped situation is likely to produce the hypertensive crisis as shown in Figure 2. Moreover, clinicians should note that in these cases, a second overdose may occur because the ratio in concentration between the saline and the norepinephrine pump is temporarily changed at the mixing point of the infusion set along with the flow rate deviation, 6 which only occurred in the norepinephrine pump in the described case.…”
Section: Advice and Clinical Considerationsmentioning
confidence: 95%
“…The work cannot be changed in any way or used commercially without permission from the journal. 3 In addition, characteristics of the infusion system may yield dosing deviations after interventions, such as a syringe exchange, 4 flow rate changes, 5,6 and vertical displacement of the pump. 7 In this case report, we describe a critical care patient receiving an accidental overdose of norepinephrine, probably caused by a pump malfunction during a syringe exchange.…”
mentioning
confidence: 99%
“…However, in recent years, ample evidence has been found [14], including a number of clinical cases and in vivo studies [59], indicating that physical effects related to the infusion hardware are equally important to understand [10, 11]. Especially in critical care, on the ICU and the OR, where multiple medications are typically delivered through one single lumen of a thin catheter, these physical effects may cause ambiguous and counter-intuitive discrepancies between the intended dose and the dose that has been actually delivered.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier paper, we have shown that the “dead volume effect” on one hand, and syringe compliance (“capacitor”) effect on the other hand, produce opposite deviations from the pump flow rate settings in the actual drug output concentrations, making the net result hard to predict and often counterintuitive [4]. …”
Section: Introductionmentioning
confidence: 99%
“…The first two contributions introduce the subject. They explain the background of metrology for drug delivery [8] and offer an overview of studies related to flow variability [16].…”
mentioning
confidence: 99%